Heat-transfer characteristics of CO2 boiling flow in the regenerative cooling channel of an Mg/CO2 powder rocket engine for Mars missions. (December 2021) - Wei, Ronggang; Hu, Chunbo; Wu, Fuzhen; Hu, Jiaming; Zhu, Xiaofei; Yang, Jiangang; Li, Fengchao; Li, Chao
Abstract: To solve the problem of thermal protection posed by the long working time of Mg/CO 2 powder rocket engines, an experimental system is designed to study the heat-transfer characteristics of liquid CO 2 in the regenerative cooling channel. How the heat flux, coolant temperature, mass flux, and back pressure influence the heat-transfer coefficient, the thermodynamic quality, and the gas-phase formation point of nearly saturated CO 2 is studied. The heat-transfer coefficient is found to increase with increasing mass flux or decreasing inlet temperature. Higher heat flux increases the rate of bubble formation and promotes nucleate-boiling heat transfer, but it also intensifies the film boiling, thereby degrading the heat-transfer performance. Lower back pressure does not affect the heat-transfer performance in the nucleate-boiling region, but it worsens it in the film-boiling region. It is also found that the classical boiling-heat-transfer models do not predict the experimental heat-transfer coefficient well. Combined with experimental data, how reduced pressure affects heat transfer is considered, and a new empirical correlation formula is proposed for the heat-transfer coefficient of CO 2 near saturation. The optimized model can successfully predict 90.23% of the experimental data, and the prediction accuracy is improved greatly. The present research provides a theoretical basis for designing a regenerative cooling scheme for an Mg/CO 2 powder rocket engine. Highlights: Liquid CO2 is used as coolant for the first time to conduct heat transfer experiments in a regenerative cooling channel. A method for calculating the heat transfer coefficient along the microchannel is established. The effects of different heat fluxes, coolant temperatures, mass fluxes and back pressures on the heat transfer performance of CO2 are obtained. An empirical correlation for heat transfer of CO2 boiling flow in a regenerative cooling channel at near saturation state is obtained.